2020
DOI: 10.3389/fimmu.2020.00697
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Protects Against Severe Influenza by Reducing the Pro-Inflammatory Cytokine Response in the Murine Lung

Abstract: Influenza A virus pathogenesis may differ between men and women. The 2009 H1N1 influenza pandemic resulted in more documented hospitalizations in women compared to men. In this study, we analyzed the impact of male sex hormones on pandemic 2009 H1N1 influenza A virus disease outcome. In a murine infection model, we could mimic the clinical findings with female mice undergoing severe and even fatal 2009 H1N1 influenza compared to male mice. Treatment of female mice with testosterone could rescue the majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
4
12
0
Order By: Relevance
“…However, our data is in line with data reported in murine models, where infection of healthy male mice with influenza A virus was shown to reduce testosterone levels by independent laboratories[10] [12]. Interestingly, treatment of female and male mice with testosterone protected animals from lethal outcome[10]. However, testosterone treatment of elderly male mice was less effective [20].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, our data is in line with data reported in murine models, where infection of healthy male mice with influenza A virus was shown to reduce testosterone levels by independent laboratories[10] [12]. Interestingly, treatment of female and male mice with testosterone protected animals from lethal outcome[10]. However, testosterone treatment of elderly male mice was less effective [20].…”
Section: Discussionsupporting
confidence: 90%
“…One limitation of this study is that we have no information regarding potential comorbidities in these groups, such as diabetes type II or obesity, which are known to lower testosterone levels in men[1619]. However, our data is in line with data reported in murine models, where infection of healthy male mice with influenza A virus was shown to reduce testosterone levels by independent laboratories[10] [12]. Interestingly, treatment of female and male mice with testosterone protected animals from lethal outcome[10].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Therefore, we used a 2009 pandemic H1N1 influenza A virus (pH1N1) isolate and an avian H7N9 influenza A virus isolated from a patient. Both, pH1N1 and H7N9 influenza virus infections mediated low testosterone levels upon infection but did not alter estradiol levels in male mice in line with previous reports 12 . Thus, the shift in sex hormones from testosteroneto-estradiol detected seems to be specific for SARS-CoV-2 infection in male animals (Extended Data Figure 4).…”
Section: Sars-cov-2 Infection Mediates Reduced Testosterone and Incresupporting
confidence: 91%
“…Second, we found that in males unlike in females, systemic reduction of testosterone levels is accompanied by elevated estradiol levels, which might additionally affect endocrine functions of the sex hormones. Control male animals infected with H1N1 and H7N9 influenza A virus presented reduced testosterone levels as shown before but not elevated estradiol levels 12 . This is in line with findings from human cohorts, where H1N1 and H7N9 influenza A virus infection in men correlated with low testosterone but not elevated estradiol levels 30 .…”
Section: Discussionsupporting
confidence: 59%